2022
DOI: 10.17576/jkmjc-2022-3802-01
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Prostitution Services on Social Media

Abstract: If in the past, promotion of sexual services was done face to face – on the streets or brothels – but now it has turned to social media. Data shows that online prostitution continues to increase because it can be accessed easily on social media. Social media, with its more open communication, is considered adequate for the promotion of commercial sex services. The purpose of this study is to get an overview of the interaction and communication with regards to online promotion of prostitutions on social media. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Research shows that social media platforms are used to promote prostitution services (Juditha et al, 2022). In addition, other studies have shown that high school students use social media for prostitution (Asur et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that social media platforms are used to promote prostitution services (Juditha et al, 2022). In addition, other studies have shown that high school students use social media for prostitution (Asur et al, 2011).…”
Section: Introductionmentioning
confidence: 99%